EFFECT OF SELF-REGULATED LEARNING ON ACADEMIC ACHIEVEMENT OF PUANGRIMAGGALATUNG UNIVERSITY EDUCATIONAL ADMINISTRATION STUDY PROGRAM STUDENTS - Sumarni Nasir; Nurhidayah Nurhidayah; Ahmad Suprianto (Universitas Ahmad Dahlan, 2020)
This study specifically investigated the factors self-regulated learning on achievement academic students of the program study the administration of the education faculty of teacher training and science education. The design of this study applies a correlational design. The population study is a student at the Faculty of teacher and science education University Puangrimaggalatung program of study administration of the education workforce in 2017 until with student class of 201 9 totaling 257 students with a total sample of 69 people. Based on the results of testing the data for the regression test, the results obtained significance = 0,000 <0.05. The hypotheses proposed are accepted that the influence of the variable self-regulation to the achievement of learning. The Hi accepted, which means no influence positively between self-regulation and achievement Akademik students of the Faculty of Teacher Training and Science Education University Puangrimaggalatung Program Study of Educational Administration Education. It demonstrated that the increasingly high self-regulation of the increasingly high achieving academic students.